Results 1 to 10 of 10

Math Help - ODE

  1. #1
    Member kjchauhan's Avatar
    Joined
    Nov 2009
    Posts
    137
    Thanks
    2

    ODE

    Pl help me to solve it..

    Solve: y'''-y''-y'+y=8te^{-t}, with the initial conditions y(0)=o, y'(0)=1 and y''(0)=0 using Laplace Transform.

    I've taken Laplace Transform,

    L(y''')-L(y'')-L(y')+L(y)=8L(te^{-t})

    \therefore p^3L(y)-p^2y(0)-py'(0)-y''(0)-p^2L(y)+py(0)+y'(0)-pL(y)+y(0)+L(y)<br />
=8\left(\frac{1}{(p+1)^2}\right)

    \therefore (p^3-P^2-p+1)L(y) = 8\left(\frac{1}{(p+1)^2}\right) +p-1

    I've simplified it but, I did not get it..

    Thanks ..
    Follow Math Help Forum on Facebook and Google+

  2. #2
    A Plied Mathematician
    Joined
    Jun 2010
    From
    CT, USA
    Posts
    6,318
    Thanks
    4
    Awards
    2
    Your work so far is fine (watch the capital P on the LHS, though). On the RHS, you can get a common denominator and add. The LHS factors, and then you can solve for L(y). What do you get?
    Follow Math Help Forum on Facebook and Google+

  3. #3
    MHF Contributor

    Joined
    Apr 2005
    Posts
    15,412
    Thanks
    1328
    Oh, dear, oh dear, oh, dear! I really dislike the Laplace Transform! It can be used in two diametrically opposite ways- to "look up" solutions to non-homogeneous equations or to assert a form of a solution in very abstract theorems. The first is more easily done in other ways and the second, undergraduates never see.

    I would look at that equation and immediately write down it characteristic equation: r^3- r^2- r+ 1= 0. It's easy to see, by inspection, that r= 1 is a root of that and that r^3- r^2- r+ 1= (r-1)(r^2- 1)= (r- 1)^2(r+ 1) so that r= 1 is a double root and r= -1 is a root. That tells us that the general solution to the associated homogeneous equation is y= Ae^t+ Bte^t+ Ce^{-t}.

    The "non-homogeneos" part is 8te^{-t}. Since te^{-t} is already a solution to the associated homogeneous equation, we try a solution of the form y= (At^2+ Bt)e^{-t}. Then y'= (At+ B)e^{-t}- (At^2+ Bt)e^{-t}= (-At^2+ (A- B)t+ B)e^{-t}, y''= (-2At+ (A- B)e^{-t})e^{-t}- (-At^2+ (A- B)t+ B)e^{-t} =(At^2+ (B- 3A)t+ A- 2B)e^{-t}, and y'''= (2At+ B- 3A)e^{-t}- (At^2+ (B- 3A)t+ A- 2B)e^{-t}= (-At^2+ (5A- B)t+ 3B- 5A)e^{-t}.

    Putting those into the differential equation will give you equations for A and B.
    Last edited by HallsofIvy; January 4th 2011 at 02:32 AM.
    Follow Math Help Forum on Facebook and Google+

  4. #4
    Member kjchauhan's Avatar
    Joined
    Nov 2009
    Posts
    137
    Thanks
    2
    Quote Originally Posted by HallsofIvy View Post
    Oh, dear, oh dear, oh, dear! I really dislike the Laplace Transform! It can be used in two diametrically opposite ways- to "look up" solutions to non-homogeneous equations or to assert a form of a solution in very abstract theorems. The first is more easily done in other ways and the second, undergraduates never see.

    I would look at that equation and immediately write down it characteristic equation: r^3- r^2- r+ 1= 0. It's easy to see, by inspection, that r= 1 is a root of that and that r^3- r^2- r+ 1= (r-1)(r^2- 1)= (r- 1)^(r+ 1) so that r= 1 is a double root and r= -1 is a root. That tells us that the general solution to the associated homogeneous equation is y= Ae^t+ Bte^t+ Ce^{-t}.

    The "non-homogeneos" part is 8te^{-t}. Since te^{-t} is already a solution to the associated homogeneous equation, we try a solution of the form y= (At^2+ Bt)e^{-t}. Then y'= (At+ B)e^{-t}- (At^2+ Bt)e^{-t}= (-At^2+ (A- B)t+ B)e^{-t}, y''= (-2At+ (A- B)e^{-t})e^{-t}- (-At^2+ (A- B)t+ B)e^{-t} =(At^2+ (B- 3A)t+ A- 2B)e^{-t}, and y'''= (2At+ B- 3A)e^{-t}- (At^2+ (B- 3A)t+ A- 2B)e^{-t}= (-At^2+ (5A- B)t+ 3B- 5A)e^{-t}.

    Putting those into the differential equation will give you equations for A and B.
    You are absolutely right, and that way I can solve this equation, But it is compulsory to solve using Laplace Trasform for me..
    Follow Math Help Forum on Facebook and Google+

  5. #5
    Member kjchauhan's Avatar
    Joined
    Nov 2009
    Posts
    137
    Thanks
    2
    <br />
(p^3-p^2-p+1)L(y) = 8\left(\frac{1}{(p+1)^2}\right) +p-1

    \therefore L(y) = \frac{\frac{8}{(p+1)^2}+p-1}{(p^3-p^2-p+1)}

    \therefore L(y) = \frac{8}{(p+1)^2(p^3-p^2-p+1)}+\frac{p-1}{(p^3-p^2-p+1)}

    \therefore L(y) = \frac{8}{(p+1)^3(p-1)^2}+\frac{p-1}{(p-1)^2(p+1)}

    \therefore L(y) = \frac{1}{(p-1)^2}+ \frac{1}{2(p+1)^3}+\frac{1}{2(p-1)}-\frac{1}{2(p+1)}

    \therefore y=L^{-1} \left( \frac{1}{(p-1)^2}+ \frac{1}{2(p+1)^3}+\frac{1}{2(p-1)}-\frac{1}{2(p+1)}\right)

    \therefore y=te^t+\frac{t^2e^{-t}}{4}+\frac{e^t}{2}+\frac{e^{-t}}{2}

    Correct???
    Last edited by kjchauhan; January 4th 2011 at 12:36 AM.
    Follow Math Help Forum on Facebook and Google+

  6. #6
    A Plied Mathematician
    Joined
    Jun 2010
    From
    CT, USA
    Posts
    6,318
    Thanks
    4
    Awards
    2
    Can you factor the cubic?
    Follow Math Help Forum on Facebook and Google+

  7. #7
    Member kjchauhan's Avatar
    Joined
    Nov 2009
    Posts
    137
    Thanks
    2
    Yes
    Follow Math Help Forum on Facebook and Google+

  8. #8
    A Plied Mathematician
    Joined
    Jun 2010
    From
    CT, USA
    Posts
    6,318
    Thanks
    4
    Awards
    2
    So how does that change your expression?
    Follow Math Help Forum on Facebook and Google+

  9. #9
    Member kjchauhan's Avatar
    Joined
    Nov 2009
    Posts
    137
    Thanks
    2
    Quote Originally Posted by Ackbeet View Post
    So how does that change your expression?
    Thank you very much..
    Follow Math Help Forum on Facebook and Google+

  10. #10
    A Plied Mathematician
    Joined
    Jun 2010
    From
    CT, USA
    Posts
    6,318
    Thanks
    4
    Awards
    2
    You're welcome. Have a good one!
    Follow Math Help Forum on Facebook and Google+

Search Tags


/mathhelpforum @mathhelpforum